Nutrient deficiency and obstetrical outcomes in pregnant women following Roux-en-Y gastric bypass: A retrospective Danish cohort study with a matched comparison group. (September 2017) - Hammeken, Lianna Hede; Betsagoo, Ramsina; Jensen, Ann Nygaard; Sørensen, Anne Nødgaard; Overgaard, Charlotte
Abstract: Objective: Roux-en-Y gastric bypass surgery and small-for-gestational-age births are known to be associated although the etiology is not fully understood. This study aimed to investigate pregnancy outcomes and maternal nutritional status among pregnant women with a history of Roux-en-Y gastric bypass using maternal anemia and gestational weight gain as indicators of micronutrient and macronutrient deficiency in pregnancy. Study design: The study was designed as a retrospective matched cohort study. All Roux-en-Y-gastric-bypass-operated pregnant women (n = 151) who were followed in the outpatient obstetric clinic at Aalborg University Hospital in Denmark and gave birth between 1 January 2010 and 31 December 2013 were included. Each Roux-en-Y-gastric-bypass-operated woman was closely matched with a non-Roux-en-Y-gastric-bypass-operated woman. Primary outcomes were small-for-gestational-age birth, maternal anemia and gestational weight gain. The two groups (matched 1:1) were compared by paired tests on all measures, conditional logistic regression for paired binary data and the paired t -test or Wilcoxon signed-rank test for paired continuous data. Results: The risk of small-for-gestational-age birth (odds ratio (OR) = 2.67, 95% confidence interval (CI); 1.04–6.82) and maternal anemia (OR = 3.0, 95% CI; 1.09–8.25) were significantly increased for the Roux-en-Y gastric bypass group compared to the non-Roux-en-Y gastric bypass group. No significant difference was found in gestational weight gain ( p  = 0.169) between women with a history of Roux-en-Y gastric bypass (11.51 kg ± 8.97 standard deviation (SD)) and non- Roux-en-Y-gastric-bypass-operated women (12.18 kg ± 6.28 SD). Conclusion: A history of Roux-en-Y gastric bypass surgery increases the risk of small-for-gestational-age birth and anemia, while a finding of differences in gestational weight gain is uncorroborated. Our findings suggest a role of micronutrient deficiency rather than reduced gestational weight gain in the etiology of small-for-gestational-age birth among women with a history of Roux-en-Y gastric bypass surgery.